PENGARUH IKLAN, KUALITAS LAYANAN DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI PADA TOKO ONLINE LAZADA - Jontro Simanjuntak (STEKOM PRESS, 2020)
Marketing is very important in understanding consumers and markets by forming products that are in accordance with the wishes of consumers and the market in order to achieve the expected image. In the marketing world it is inseparable from advertising that can help in promoting products in a marketing, as well as the level of service quality that is able to maintain and brand trust of consumers who have a close relationship to marketing. In this study aims to determine how the influence of Advertising, Service Quality and Brand Trust On Purchase Interest in Lazada Online Stores. The sample is determined using the Isaac and Michael formula with a sample of 270 respondents, and the sampling technique uses purposive sampling, then testing the hypothesis with the support of SPSS application version 22. The advertising variable has a significance value of 0,000 <0.05 alpha and a t value of 12,951> 1,969 values t table. The service quality variable has a significance value of 0,048 <0.05 alpha and t count value is 1.984> 1.969 t table value. The variable of brand trust has a significance value of 0,033 <0.05 alpha and t count value of 2.140>1.969 t table value. Simultaneous advertisement, service quality and brand trust are f table equal to 147,136> 2,64 table f value, and sig <alpha with 0,000> 0,05.